The Concept of Disaster in Islamic Perspective: An Analysis of QS. Ar-Rum: 41, QS. Asy-Syura: 30, QS. Al-Anfal: 25, QS. Taubah: 126, and Authentic Hadiths - Na’iem, Muharrir; Zaid, Muhammad; Ustar, Nur Aisyah; Rahmaniah, Rahmaniah; Amaluddin, Amaluddin (The Future of Education Journal, 2026)
Disasters are recurring phenomena in human life and have multidimensional impacts, including physical, social, and spiritual effects. This article aims to examine the concept of disaster from an Islamic perspective based on the Qur'an and authentic Hadiths, as well as to explore the theological and educational meanings contained therein. This research uses a qualitative approach with a library research method, through analysis of verses from the Qur'an, specifically QS. Ar-Rūm: 41, QS. Asy-Syūrā: 30, QS. Al-Anfāl: 25, and QS. At-Taubah: 126, as well as authentic Hadiths related to calamities, repentance, and patience. The results of the study show that Islam views disasters as the result of human actions, a test of faith, a collective warning, and a means of divine education to encourage repentance and self-improvement. Disasters are not merely understood as punishment, but also as a form of mercy and an opportunity for moral and social transformation. The implications of this study emphasise the importance of integrating Islamic values into disaster education and strengthening Islamic character in order to build awareness of human responsibility as caliphs on earth.